Learning in context: Technology integration in a teacher preparation program informed by situated learning theory - Bell, Randy L.; Maeng, Jennifer L.; Binns, Ian C. (Journal of research in science teaching, 2013)
This investigation explores the effectiveness of a teacher preparation program aligned with situated learning theory on preservice science teachers' use of technology during their student teaching experiences. Participants included 26 preservice science teachers enrolled in a 2‐year Master of Teaching program. A specific program goal was to prepare teachers to use technology to support reform‐based science instruction. To this end, the program integrated technology instruction across five courses and situated this instruction within the context of learning and teaching science. A variety of data sources were used to characterize the participants' intentions and instructional practices, including classroom observations, lesson plans, interviews, and written reflections. Data analysis followed a constant comparative process with the goal of describing if, how, and why the participants integrated technology into their instruction and the extent to which they applied, adapted, and innovated upon what they learned in the science teacher preparation program. Results indicate that all participants used technology throughout their student teaching for reform‐based science instruction. Additionally, they used digital images, videos, animations, and simulations to teach process skills, support inquiry instruction, and to enhance student engagement in ways that represented application, adaptation, and innovation upon what they learned in the science teaching methods program. Participants cited several features of the science teacher preparation program that helped them to effectively integrate technology into their instruction. These included participating in science lessons in which technology was modeled in the context of specific instructional approaches, collaborating with peers, and opportunities for feedback and reflection after teaching lessons. The findings of this study suggest that situated learning theory may provide an effective structure for preparing preservice teachers to integrate technology in ways that support reform‐based instruction. © 2013 Wiley Periodicals, Inc. J Res Sci Teach 50:348–379, 2013